Geometry and Maintenance Analysis of All Wheater Road (AWR) TS +35 to TLS 2 Tambang Air Laya, PT. Bukit Asam, Tbk. Anjung Enim, South Sumatera - Fathi Aulia Dhanio Zuhri; Heri Prabowo (Journals Mining Engineering : Bina Tambang, 2024)
Indonesia has many coal resources that can play an important role in meeting domestic energy needs. The mining system applied by PT Bukit Asam Tbk is open mining with open pit mining method. The mining industry is one of the industries that is capital intensive, technology intensive, and very risky. One of the important things in mining activities is coal transportation to achieve production targets. Some factors that affect the conveyance cannot operate optimally include narrow haul road conditions so that when the conveyance passes one of the conveyances must stop, bumpy road conditions so that during transportation a lot of material is scattered. the purpose of this study is to control the condition of the haul road to be traversed so that production targets and operator safety in the mining area can be maintained properly. The width of the haul road in straight and bend conditions is different, the width of the mine road on the bend is always made larger than the straight road. This is intended to anticipate deviations in haul road width caused by the angle formed by the front wheels with the truck body when crossing the curve. A good mine road has a transverse slope between 20 mm/m and 40 mm/m or 2% to 4% for every 1m of mine haul road width. From the results of the calculations that have been carried out, the haul road geometry on the TS +35 to TLS 2 road has a length of 3,125 m by making as many as 5 segments, namely 10 straight road sections and 6 bend road segments. On the straight road there are 2 sections whose road width still does not meet the standards of Kepmen No. 1827/K/30/MEM/2018, which will have an impact on the performance of the conveyance used and can cause human error when vehicles pass each other. Meanwhile, the width of the bend road and the cross slope value on several road sections have met the road standards.